2022
DOI: 10.3390/en15103737
|View full text |Cite
|
Sign up to set email alerts
|

Renovation of Modernist Housing Developments in the Pursuit of Modernity for Well-Being and Clean Energy

Abstract: The research concerns renovation variants for modernist housing estates built in Szczecin, Poland during 1918–1925 and in Bialystok, Poland during 1950–1990. These buildings are now substandard in many ways; functionally, aesthetically, technically, and ecologically they do not fulfil the current energy efficiency standards. Some of them have architectural heritage, so not all energy-saving technologies can be applied. Renovations must include energy-saving improvements and the use of renewable energy sources.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…This is a pressing problem, especially in the context of achieving the "Fit for 55" goals. Turecki et al (2022) indicated that, for multi-family buildings, Poland should aim to achieve a higher level of CO 2 reduction than the expected 55% target, since the reduction rate for single-family housing is likely to be much lower.…”
Section: Beneficiaresmentioning
confidence: 99%
“…This is a pressing problem, especially in the context of achieving the "Fit for 55" goals. Turecki et al (2022) indicated that, for multi-family buildings, Poland should aim to achieve a higher level of CO 2 reduction than the expected 55% target, since the reduction rate for single-family housing is likely to be much lower.…”
Section: Beneficiaresmentioning
confidence: 99%
“…International regulatory and financial support has played a key role here, as has the EU accession process more specifically. A number of states in Central Europe have advanced ambitious housing renovation programmes, while improving the depth and targeting of social support mechanisms (Földváry et al, 2017; Hrovatin and Zorić, 2018; Turecki et al, 2022). Elsewhere in the region – and particularly in non-EU post-socialist states – energy poverty remains pervasive, and has been further worsened by trends unfolding during the post-socialist transformation: political instability and military conflict, declining real incomes, increasing social inequalities, and slow progress on the upgrading of the housing stock and energy systems (Maxim et al, 2017; Stojilovska et al, 2021).…”
Section: Domestic Energy Inequalities In Post-socialism: Emergent Geo...mentioning
confidence: 99%